Transactional and transformational leadership in context of Malaysian construction industry - Chong, Ming Yang (2003)
The pace of changing global environment is hectic and we forced to face the future with lot of uncertainties. Given this situation, competence technical and broad managerial abilities are remaining important but not more than leadership. The objectives of this study were to study and compare the leadership behaviour underlying the leader and subordinates' preference leadership behaviour in context of Malaysian construction industry with respect to transactional leadership and transformational leadership. This research also studied interrelationship between subordinates' preference leadership behavior corresponding with subordinates' working experience, comparison between the leadership behaviour underlying the leaders between Consulting Firms and Contracting Firms as well as comparison between subordinates' preference leadership behaviour between Consulting Firms and Contracting Firms. A total of 80 questionnaires d m from construction-related Technical Professional were collected and used. Frequency counts of the responses were computed, from which the mean score for each item was calculated. The relative importances were then ranked form the highest to the lowest for each topic concerned. The result shows that the leaders tended to demonstrate transformational leadership along with the subordinates also preferred transformational leadership. However the exercising degree of transfornational leadership by the leaders was much lower than subordinates' expectation. The fmding is aimed at providing a basic guidance and usell information for Malaysian construction industry leaders to have a better understanding as to followers' satisfaction.